USE OF COMPOUND SPECIFIC ISOTOPE ANALYSIS TO DIFFERENTIATE SOURCES OF INDOOR AIR CONTAMINATION - Bouchard, Daniel; R. Gouvea Jr., José Carlos; Henderson, James K. (Águas Subterrâneas, 2019)
The use of Compound Specific Stable Isotopes (CSIA) in environmental applications is well known, and typically centers on verifying biodegradation or lending a forensic component to environmental assessments (i.e., determining ownership of releases). Following successful CSIA applications on volatile organic compounds (VOC) dissolved in groundwater, there is increasing interest in the use of CSIA to assess VOC in gas-phase, such as to evaluate vadose zone attenuation processes and the potential differentiation of sources of indoor air contamination. New methodologies for collection and analysis of vapor-phase samples from the indoor air are presented. Potential applications and field studies will be summarized, as well as their potential relevance and use in Brazil.